In Silico Analysis of the Biomechanical Stability of Commercially Pure Ti and Ti-15Mo Plates for the Treatment of Mandibular Angle Fracture - Yamaguchi, Satoshi; Anchieta, Rodolfo B.; Guastaldi, Fernando P.S. [UNESP]; Tovar, Nick; Tawara, Daisuke; Imazato, Satoshi; Coelho, Paulo G. (Elsevier, 2017)
Purpose To investigate the influence of different materials and fixation methods on maximum principal stress (MPS) and displacement in reconstruction plates using in silico 3-dimensional finite element analysis (3D-FEA). Materials and Methods Computer-assisted designed (CAD) models of the mandible and teeth were constructed. Champy and AO/ASIF plates and fixation screws were designed with CAD software. 3D-FEA was performed by image-based CAE software. Maximum and minimum values of biomechanical stability, MPS, and displacement distribution were compared in Champy and AO/ASIF plates made from commercially pure titanium grade 2 (cp-Ti) and a titanium-and-molybdenum (14.47% wt) alloy (Ti-15Mo). Results For plates fixed on a model of a fractured left angle of the mandible, the maximum and minimum values of MPS in the cp-Ti–constructed Champy plate, upper AO/ASIF plate, and lower AO/ASIF plate were 19.5 and 20.3%, 15.2 and 25.3%, and 21.4 and 4.6% lower, respectively, than those for plates made from Ti-15Mo. In the same model, the maximum and minimum values of displacement in the cp-Ti–constructed Champy plate, upper AO/ASIF plate, and lower AO/ASIF plate were 1.6 and 3.8%, 3.1 and 2.7%, and 5.4 and 10.4% higher, respectively, than those for plates made from Ti-15Mo. Conclusions This in silico 3D-FEA shows that Ti-15Mo plates have greater load-bearing capability.